Genotype and Phenotype Characterization of Indonesian Phytophthora infestans Isolates Collected From Java and Outside Java Island - Dwinita Wikan Utami; Dinar Ambarwati (HAYATI Journal of Biosciences, 2017)
Phytophthora infestans, the cause of late blight disease, is a worldwide problem in potato and tomato production. To understand the biology and ecology of P. infestans and the mechanism of spatial and temporal factors for the variation in P. infestans, the population diversity is required to be fully characterized. The objective of this research is to characterize the diversity of P. infestans. Surveys and collection of P. infestans isolates were performed on many locations of potato's production center in Indonesia, as in Java (West Java, Central Java, and East Java) and outside of Java islands (Medan, Jambi, and Makassar). The collected isolates were then analyzed for their virulence diversity via plant disease bioassays on differential varieties and genotype diversity based on fragment analysis genotypes profile using the multiplexing 20 simple sequence repeat markers. The virulence characterization showed that the isolates group from Makassar, South Sulawesi, have the broad spectrum virulence pathotype to R1, R2, R3, R4, and R5 differential plants. Simple sequence repeat genotype characterization showed that in general, the population structure of P. infestans grouping is accordance to the origin of the sampling locations. The diversity between populations is lower than diversity between isolates in one location population groups. The characters of P. infestans population showed that the population diversity of P. infestans more occurs on individual isolates in one location compared with the diversity between the population location sampling.